Astrological Parlance of Macro and Micro Nutrients - Pawar, Rajendra Singh; Dimri, Mayank; Kush, Luv (Asian Journal of Pharmaceutical Research and Development, 2020)
The dietary minerals are astro-elements . They maintain normal biochemical physiology and anatomical strength. Their deficiencies under unfavorable planetary configurations cause health-maladies.